The Effect of Spiritual Therapy on Resiliency of Hemodialysis Patients - Peiman Fereidouini sarijeh; Behdokht Kia; Mehdi Mahmoodi; Mahsa Salahi Nejad (Hamadan University of Medical Sciences, 2021)
Background and Objective: People with high resilience evaluate stressful events as more positive and controllable than people with low resilience. The aim of this study was to determine the effect of spirituality therapy on the resilience of patients undergoing hemodialysis. Material and Methods: The present study is a quasi-experimental study with two experimental and control groups. The statistical population of the study consisted of all patients undergoing hemodialysis referred to Imam Reza (AS) Hospital and Imam Ali (AS) Hospital in Amol, Iran. The participants of the present study included 80 patients undergoing hemodialysis who were divided into experimental (n = 40) and control (n = 40) groups. The research instruments were demographic information self-report questionnaires, Connor and Davidson Resilience Scale. Patients in the intervention group participated in 12 sessions of spiritual therapy and therapy individually and with respect to patient privacy for 6 weeks. Data analysis was performed using SPSS 24 software. Results: In the control group, before the intervention, the mean and standard deviation of resilience scores were 33.70 ± 3.6, which after the intervention, the resilience score was 33.77.±2.8. The results of paired t-test showed that there was no statistically significant difference between resilience scores in the control group before and after the intervention (P>0.05) and in the intervention group before and after the intervention, a statistically significant difference was observed between resilience scores. (P<0/001). Conclusion: The results of this study indicated that spiritual therapy can be effective in increasing the resilience of patients undergoing hemodialysis.